A pharmacokinetic study comparing the biosimilar HEC14028 and Dulaglutide (Trulicity®) in healthy Chinese subjects - Xianglei Gao; Yujing Di; Yuan Lv; Yingcai Luan; Yang Xiong; Yuli Xu; Yusheng Li; Linfeng Guo; Xiaoping Li; Li Deng; Yulei Zhuang; Jie Hou (Wiley, 2024)
Abstract This study aimed to evaluate the pharmacokinetics (PKs), safety, and immunogenicity of the biosimilar HEC14028 compared to reference Trulicity® (dulaglutide) in healthy male Chinese subjects. This study was a single‐center, randomized, open, single‐dose, parallel‐controlled comparative Phase I clinical trial, including a screening period of up to 14 days, a 17‐day observation period after administration, and a 7‐day safety follow‐up period. A total of 68 healthy male subjects were randomly assigned (1:1) to the test group (HEC14028) and the reference group (dulaglutide) (single 0.75 mg abdominal subcutaneous dose). The primary objective was to evaluate the pharmacokinetic characteristics of HEC14028 and compare the pharmacokinetic similarities between HEC14028 and dulaglutide. The primary PK endpoints were maximum plasma concentration (Cmax) and area under the blood concentration‐time curve from zero time to the estimated infinite time (AUC0-∞). The study results showed that HEC14028 and dulaglutide were pharmacokinetically equivalent: 90% confidence interval (CI) of Cmax and AUC0-∞ geometric mean ratios were 102.9%-122.0% and 97.1%-116.9%, respectively, which were both within the range of 80.00%-125.00%. No grade 3 or above treatment emergent adverse events (TEAEs), serious adverse events (SAEs), TEAEs leading to withdrawal from the trial, or TEAEs leading to death were reported in this study. Both HEC14028 and dulaglutide showed good and similar safety profiles, and no incremental immunogenicity was observed in subjects receiving HEC14028 and dulaglutide.